1996
DOI: 10.1002/(sici)1097-010x(19961015)276:3<201::aid-jez4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cell number regulation in the peri-implantation mouse blastocyst

Abstract: Low viability of manipulated or in vitro cultured embryos is caused primarily by the reduced cell number in the implanting blastocysts. In order to investigate the effect of implantation delay on embryo viability and cell number, mouse blastocysts were transferred into oviducts of day 0 pseudopregnant females. This type of transfer improved embryo survival rates, indicating that embryos retarded by in vitro culture restored their viability during 3 days of delayed implantation. Our results showed that even in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
3
1
1
Order By: Relevance
“…Moreover, asynchronously transferred blastocysts into oviduct of a 0.5-dpc female, or synchronously transferred into the uterus of a 2.5-dpc female, resulted in differences in weight of fetuses recovered 13 days after the embryo transfer, indicating that blastocysts transferred into the oviduct implant later than embryos transferred into the uterus. In agreement with previous work [28], we have found that the implantation delay increases blastocyst cell number and allows them to develop beyond the hatching blastocyst stage. However, these embryos went into diapause in the hatched blastocyst stage.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, asynchronously transferred blastocysts into oviduct of a 0.5-dpc female, or synchronously transferred into the uterus of a 2.5-dpc female, resulted in differences in weight of fetuses recovered 13 days after the embryo transfer, indicating that blastocysts transferred into the oviduct implant later than embryos transferred into the uterus. In agreement with previous work [28], we have found that the implantation delay increases blastocyst cell number and allows them to develop beyond the hatching blastocyst stage. However, these embryos went into diapause in the hatched blastocyst stage.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the ICM cell to TE cell ratio was somewhat lower than that obtained from other studies using different mouse strains [6,7]. This may be due to the strain specificity or the loss of some ICM cells during the labeling of the blastocyst.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, we employed a continuous culture system for establishing a high embryo per volume ratio, but the accumulation of embryotoxic substances in culture system may be possible. For example, accumulating ammonia of a final product of amino acid metabolism may be responsible for lowing the ratio of ICM cells to trophectodermal cells [6,12]. An alternative strategy such as the employment of a sequential culture system and the use of culture medium containing the detoxicants for embryotoxin may further promote the growth of blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…So the decreased cell number of blastocyst may result from the retarded cell division in the stage. The fewer number of cells means delayed and poor development (Evsikov et al, 1996;Goossens et al, 2006). It is well known that a critical threshold number of cells in blastocysts is required for normal postimplantation development.…”
Section: Discussionmentioning
confidence: 99%